Aplastic or twig-like middle cerebral artery and cardiogenic cerebral embolism mimicking moyamoya disease with RNF213 polymorphism: A case report. Issue 6 (December 2022) - Inoue, Hiroyasu; Oomura, Masahiro; Nishikawa, Yusuke; Mase, Mitsuhito; Matsukawa, Noriyuki
Progressive stenosis and occlusion of the bilateral internal carotid artery terminals and circle of Willis are typical features of Moyamoya disease. However, aplastic or twig-like middle cerebral artery (Ap/T-MCA)—wherein the unilateral main trunk of the middle cerebral artery (MCA) is not depicted, and a plexiform arterial network is formed—is similar to the findings of Moyamoya disease. Here, we describe a 78-year-old man who presented with mild right paralysis and aphasia. Magnetic resonance angiography (MRA) at admission did not show the bilateral MCAs. The findings were similar to those of Moyamoya disease, and his symptoms worsened after hospitalization. Endovascular treatment was performed, and the left MCA was completely recanalized. Later, paroxysmal atrial fibrillation was detected, and we finally determined that left MCA occlusion had occurred due to embolism. The right MCA was completely occluded at its origin, indicating an Ap/T-MCA. Embolic occlusion of the unilateral MCA and contralateral Ap/T-MCA made this case resemble Moyamoya disease in the acute stage. Even when chronic occlusion is suspected on MRA in acute cerebral infarction, endovascular treatment should be considered. Additionally, a heterotypic R4810K polymorphism was later found in the RNF213 gene. To our knowledge, this is the second report of Ap/T-MCA with the RNF213 gene polymorphism; however, their association remains unclear and requires further analyses.